Development of Interactive E-LKPD Based on Process Oriented Guided Inquiry Learning (POGIL) - Wulandari, Melynda Sri; Dewi, Retno Mustika (Jurnal Ecogen, 2025)
This study aims to determine (1) the criteria for developing E-LKPD teaching materials designed to evaluate economics learning based on Process Oriented Guided Inquiry Learning (POGIL) and (2) their effectiveness in improving students' academic performance, evaluated through pre-tests and post-tests. This study adopts development research design utilizing the ADDIE model, comprising five stages: analyze, design, development, implementation, and evaluation. The product trial involving 62 grade XI students at SMAN 18 Surabaya was executed using a non-equivalent control group design. The data were analyzed applying the N-Gain Score Test and Independent Sample t-test. The results indicate that the average validation score from material and media experts was 86.7%, categorized as “Very Feasible”. Student responses averaged 89%, and teacher responses averaged 90.5%, both deemed as “Very Practical”. The N-Gain Score test yielded a score of 77.2%, categorized as effective, and the Independent Sample t-test indicated a significance level of 0.001 < 0.05. Therefore, it can be concluded that the E-LKPD based on POGIL is effective in enhancing students' learning outcomes.